Juvenile Myelomonocytic Leukemia: Experience from a Tertiary Care Hospital in Eastern India - Ghosh, Kaustav; Bhattacharya, Subham; Roy, Shipla; Mandal, Prakas Kumar; Sharma, Abhishek; Baul, Shuvraneel; Saha, Sandeep; De, Rajib; Dolai, Tuphan Kanti (Asian Pacific Journal of Cancer Care, 2024)
Background and objective: Juvenile myelomonocytic leukemia (JMML), previously known as juvenile chronic myeloid leukemia, is a rare, aggressive myeloproliferative neoplasm primarily affecting early childhood. Diagnosing JMML can be challenging due to overlapping clinical and hematological features with other myeloproliferative neoplasms (MPNs). However, unique characteristics such as monocytosis, the absence of BCR-ABL translocation, and the presence of specific mutations (PTPN-11, K-RAS, N-RAS, CBL, or NF1) aid in confirming the diagnosis. Material and methods: This prospective analysis included six JMML patients with varying clinical features treated with injection azacytidine as frontline therapy over a two-year study period. Results: The median age at diagnosis was 4.5 years, with a male-to-female ratio of 2:4. Pallor and splenomegaly were the most common presenting signs. Four patients (66.67%) achieved complete remission (CR), two patients (33.33%) had partial remission (PR), and one patient (16.67%) experienced progressive disease (PD). The overall survival rate was 66.67% (four out of six), and the mortality rate was 33.33%. Conclusion: Azacitidine can be an effective treatment option as frontline therapy for JMML, particularly in resource-limited developing countries.